Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Two Stay-Two Stray (TS-TS) terhadap Hasil Belajar dan Aktivitas Belajar Siswa pada Pokok Bahasan Koloid - Leony Sanga Lamsari Purba (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2017)
This study aims to determine the effect of the application of cooperative learning model two stay-two stray towards learning outcomes and learning activities of students on the subject of colloids in the 2nd half of class XI SMAN 2 Sidikalang. This type of research is an experimental research. The study population was all students in grade XI natural sciences at SMAN 2 Sidikalang. Samples were taken at random as much as 2 classes and student samples randomly assigned 40 people per class. This study uses the initial and final test design randomized control group, where both classes were given a different treatment, a class using Learning Model Two Stay-Two Stray, and one other class using conventional learning model in the form of group discussions. Based on the results of data processing, obtained an average improvement of learning outcomes in the experimental class = 70.00%, while the control class = 46.32%. Testing the hypothesis on learning outcomes is done by using the t test (the test right) with α=0.05, db = 78 obtained t (3.98)> t table (1.68). This indicates that the t arithmetic is outside the reception Ho Ha accepted meaning. Likewise with the hypothesis of the learning activities of students, Ho was rejected because at α = 0.05, db = 78 obtained t (2.87)> t table (1.68)., It can be stated that there is the effect of the application of cooperative learning model two stay-two stray towards learning outcomes and learning activities of students on the subject of colloids in the 2nd half of class XI SMA N 2 Sidikalang. This type of research is an experimental research. The study population was all students in grade XI natural sciences at SMAN 2 Sidikalang. Results of processing data correlate with the learning outcomes of students learning activities obtained positive correlations were low and the experimental class is r = 0.44. Keywords : Cooperative Learning Model’s, Two Stay-Two Stray, Learning of Activities